The Impact of Collaborative Strategic Reading (CSR) on the Students’ Reading Comprehension - Aminah Erita Purnadesia; Mahendra Puji Permana Aji; Khoiriyah Khoiriyah (UM Purwokerto Press, 2023)
The researcher found some problems of students in reading comprehension. The classroom was also quite crowded, boisterously, and students bored. The aims of this research are to know whether there is any significant effect of using Collaborative Strategic Reading (CSR) on the student reading comprehension. To explained the impact of using Collaborative Strategic Reading (CSR), the researcher used pre-experimental research and quantitative approach with one group pretest and posttest. This research was conducted at SMAN 6 Kediri. The subject of this research is first grade students and the sample consist of 36 students. The result of this research showed that t-score is higher than t-table in the level significant of 0,000. The mean score of pretest is 57,77 and the mean of posttest is 87,77. The result of this research shows that there is any significant effect of using Collaborative Strategic Reading (CSR), it is proven by the different score between pretest and posttest. This strategy helps the students to solve their problem in reading comprehension. The students are able to understand the text easily and enjoy learning.